Multimodality Imaging in Carotid Web - Madaelil, Thomas P.; Grossberg, Jonathan A.; Nogueira, Raul G.; Anderson, Aaron; Barreira, Clara; Frankel, Michael; Haussen, Diogo C. (Frontiers in Neurology, 2019)
Purpose: Carotid web (CaW) is an underrecognized cause of cryptogenic stroke in young patients. The optimal imaging for CaW is unknown. We aim to evaluate the diagnostic accuracy of diverse imaging modalities for the diagnosis of CaW. Methods: Retrospective analysis of institutional neurovascular database was performed to identify patients with multimodal (CT angiogram–CTA, digital subtraction angiogram–DSA, and/or ultrasound–US) imaging diagnosis of CaW or atherosclerosis. Baseline clinical demographics were recorded. Blinded image analysis was performed for each imaging modality by separate readers. Discrepancies were settled by consensus. Two-sided Cohen’s Kappa (κ) coefficient was used to evaluate the inter-rater agreement for the etiological diagnosis between imaging modalities. Results: Thirty patients/60 carotids were evaluated by CTA and 55 carotids were included. Patients with symptomatic CaW (n=20), compared to individuals with atherosclerosis (n=10), were younger (499 vs 608 years; p<0.01), more commonly female (75%vs. 30%;p=0.01), and less frequently presented vascular risk factors: Hypertension (40%vs. 100%;p<0.01), hyperlipidemia (0%vs. 50%;p<0.01), diabetes (10%vs. 40%;p=0.05), and smoking (5%vs. 70%;p<0.01). High inter-rater correlation strength existed for CTA (n=55; κ=0.88; p<0.0001) and DSA (n=28; κ=0.86, p<0.0001) readers for lesion diagnosis while US inter-rater agreement was lower (κ=0.553; p=0.001). Across modalities CTA and DSA shared very high strength of agreement (κ=0.92; p<0.0001), compared to a less pronounced agreement between US and CTA (κ=0.553; p=0.001). The strength of correlation between DSA-CTA was significantly more robust as compared to US-CTA (Z= 3.58;p=0.0003). Conclusion: CTA and DSA demonstrated comparable and superior performance as compared to US in the diagnosis of CaW.